A new definition and three categories for classifying ecosystems - Jaime Gómez-Márquez (Academia Biology)
The ecosystem is an essential biological concept that links the living and the inanimate. Its study has become pivotal to the analysis of global changes and environmental impacts caused by human activities and population growth. The simplest definition of ecosystem refers to a specific community of organisms that interact with each other and with their environment. However, this definition says nothing about the open character of ecosystems, about the hierarchy among species and processes, or about their capacity to evolve as a whole throughout the history of life on this planet. Here, I first take a new look at the concept of ecosystem based on the elements that in my opinion characterize it, emphasizing the importance of viruses as components of biodiversity. Secondly, I propose three categories for the global categorization of ecosystems according to the degree of human intervention. Category 1 is any undisturbed natural ecosystem. Category 2 includes ecosystems altered by humans due to socioeconomic development and population growth, causing environmental degradation and biodiversity loss. Category 3 covers all ecosystems that have been altered by the introduction of synthetic or modified organisms generated in the laboratory, the consequences of which are much more difficult to predict. Knowledge of the global distribution of these categories would help to plan global environmental policies that would contribute to making the development of our society compatible with the preservation of biodiversity